ANALISIS KOMPARATIF KINERJA KEUANGAN PT INDORITEL MAKMUR INTERNASIONAL Tbk PERIODE 2016-2020 - Dwi Sinta; Berlian Afriansyah (Politeknik Raflesia Press, 2021)
ABSTRACT-The purpose of this study was to determine financial performance through financial ratios, namely profitability ratios and solvency ratios. The secondary data used is obtained from the annual report of PT Indoritel Makmur Internasional Tbk for the 2016-2020 period which consists of Return On Assets (ROA), Return On Equity (ROE), Debt Equity Ratio (DER) and Debt Ratio. Financial performance analysis is carried out comparatively by comparing financial ratios during the 2016-2020 period and by comparing the financial ratios of PT Indoritel with similar companies, namely PT Alfaria Sumber Trijaya Tbk. The results of the analysis show that the Profitability Ratios of PT Indoritel, namely ROA and ROE, have a downward trend during the 2016-2020 period, but the solvency ratios, namely DER and Debt ratios, show an increasing trend during the 2016-2020 period, while for comparative analysis using the ratio comparison of similar companies, namely PT Alfaria Sumber Trijaya Tbk shows that for the profitability ratio, PT Alfaria is better than PT Indoritel, on the contrary for the Solvency Ratio, namely DER and Debt Ratio, PT Indoritel is better than PT Alfaria Sumber Trijaya Tbk.